Peningkatan Kemampuan Berpikir Analitis Siswa Menggunakan Lembar Kerja Siswa (LKS) Metode Penemuan Terbimbing - Agus Budi Upoyo (Pendidikan IPS FKIP ULM, 2022)
Every day, the economic problems that exist in society are always changing. Meanwhile, solving it requires the ability to think analytically. Observations at school showed that the value of the analytical thinking ability of X IPS 5 students can be said to be low. One of the reasons is that students often only get questions up to the cognitive aspect, not the analytical aspect. So far, the average economic teachers at SMA Negeri 1 Lawang still teach by lecturing, whilst daily economic problems are only conveyed orally. As the result, many students still have difficulty understanding the contextual problems. Therefore, in this study, the Student Worksheet (LKS) was used as a medium to assist students in analyzing a concept with facts. This study used a guided discovery learning method as a learning method. This study used Classroom Action Research (CAR) which consists of two cycles with two meetings. The purpose of this study was to improve students' analytical thinking skills using Student Worksheets (LKS) with the guided discovery learning method. Data collection was carried out using an analytical thinking ability test. The results showed that the economic worksheets using the guided discovery learning model improved students' analytical thinking skills with an average score of 76.11 in the first cycle and an increase in the average score of 81.1 in the second cycle. Keywords: Analytical Thinking, Worksheet, Guided Discovery Learning